2016
DOI: 10.5539/res.v8n2p224
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Factors Affecting the Effectiveness of Internal Auditors in the Company: Case Study Iran

Abstract: There are relatively fewer number of studies focused on internal audit effectiveness, than the number of studies on the effectiveness of external audit. Our focus in this paper is mainly on determinants of internal audit effectiveness. For this purpose we developed and tested five hypotheses using an investigation approach. We gathered our data using a questionnaire, filled out by 355 internal audit manager and 272 other internal audit staff.Our multivariate regression model estimates the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 15 publications
5
35
0
1
Order By: Relevance
“…Various studies have been conducted to examine the internal auditors' effectiveness (Alzeban & Gwilliam, 2014;Badara & Saidin, 2013;Erasmus & Coetzee, 2018;Salehi, 2016). However, there is no a consensus regarding the measures used to evaluate internal auditors' performance.…”
Section: Internal Auditors' Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies have been conducted to examine the internal auditors' effectiveness (Alzeban & Gwilliam, 2014;Badara & Saidin, 2013;Erasmus & Coetzee, 2018;Salehi, 2016). However, there is no a consensus regarding the measures used to evaluate internal auditors' performance.…”
Section: Internal Auditors' Effectivenessmentioning
confidence: 99%
“…The factors that influence the effectiveness of internal auditors have been seen as a controversial issue. In this regard, numerous factors have been addressed by several studies to investigate the ineffectiveness of IAF (Alzeban & Gwilliam, 2014;Salehi, 2016;Tackie et al, 2016). For example, Ahmad, Othman, Othman, & Jusoff (2009) found that lack of internal auditors' competence, understaffed departments and limited resources, lack of independence, negative view towards the role of internal audit by the auditees, and lack of the support from top management adversely impact on the effectiveness of internal audit.…”
Section: Factors Affecting the Internal Auditors' Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations